Shared vision and autonomous motivation vs. financial incentives driving success in corporate acquisitions - Clayton, Byron C. (Frontiers in Psychology, 2015)
Successful corporate acquisitions require its managers to achieve substantial performance improvements in order to sufficiently cover acquisition premiums, the expected return of debt and equity investors, and the additional resources needed to capture synergies and accelerate growth. Acquirers understand that achieving the performance improvements necessary to cover these costs and create value for investors will most likely require a significant effort from mergers and acquisitions (M&A) management teams. This understanding drives the common and longstanding practice of offering hefty performance incentive packages to key managers, assuming that financial incentives will induce in-role and extra-role behaviors that drive organizational change and growth. The present study debunks the assumptions of this common M&A practice, providing quantitative evidence that shared vision and autonomous motivation are far more effective drivers of managerial performance than financial incentives.